Developing a Framework to Measure Competency Levels of Students with Special Needs to Attend Advanced Vocational Courses - et al., Hishamuddin Ahmad (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: Students with special needs (MBK) should not be considered students who fail or have no future. Although MBKs are those with intellectual problems or shortcomings, they may have strengths or powers in other areas that need to be identified and improved. The respondents who were the sample of this study were 44 people consisting of MBK with intellectual disability, dyslexia, and visual impairment. This research employed instruments of academic success perception (α = 0.78, construct validity = 0.85), multiple intelligences (α = 0.86, construct validity = 0.87), and interview protocol to recognise the dominant aspects of MBK to build further the framework of courses advanced/vocational following the interests of the respondents. The dominant aspect for the perception of academic success was External / Future (μ = 3.43, SD = 0.38), while the most dominant aspect for multiple intelligences was Visual-Spatial Intelligence (μ = 3.22, SD = 0.46). The dominant aspects were also very relevant to MBK’s choice of advanced/vocational courses, particularly cooking, bakery, sewing, carpentry, entrepreneurs, logistics, and mechanics. It is hoped that this study’s conclusions can present information on the courses that are the authentic choice among MBKs for consideration by stakeholders in offering advanced/vocational courses to this group.